2013
DOI: 10.3109/02770903.2013.857683
|View full text |Cite
|
Sign up to set email alerts
|

Absence of gargling affects topical adverse symptoms caused by inhaled corticosteroids in females

Abstract: Objective: Topical adverse events caused by inhaled corticosteroids (ICS) are suspected to be more common in females. Although gargling or mouth washing after inhalation is recommended as the gold standard for preventing adverse events due to ICS, the preventive effects of this method have not been confirmed in real-world studies. This study aimed to examine the association between gargling or mouth washing and the incidence of topical adverse symptoms in males and females in daily practice. Methods: We analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Ruffin et al reported that 56% of the emitted aerosol dose was deposited in the oropharynx, and this might persist in situ for up to 3 hours, and that a prompt mouthwash could remove 60% of this residue from the oropharynx. There were two previous studies on local adverse effects caused by inhaled drugs . In a study by Kajiwara et al with 892 patients with bronchial asthma, the absence of RMOG after ICS was associated with topical adverse symptoms.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ruffin et al reported that 56% of the emitted aerosol dose was deposited in the oropharynx, and this might persist in situ for up to 3 hours, and that a prompt mouthwash could remove 60% of this residue from the oropharynx. There were two previous studies on local adverse effects caused by inhaled drugs . In a study by Kajiwara et al with 892 patients with bronchial asthma, the absence of RMOG after ICS was associated with topical adverse symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…There were two previous studies on local adverse effects caused by inhaled drugs . In a study by Kajiwara et al with 892 patients with bronchial asthma, the absence of RMOG after ICS was associated with topical adverse symptoms. They reported that the absence of gargling or mouth washing was identified to be a risk factor in females only and not in males, when stratified by gender in the multiple regression model .…”
Section: Discussionmentioning
confidence: 98%
“…However, some local side effects such as oral candidiasis, coughing at the time of inhalation, and hoarseness have been reported [2]. Some of these local adverse reactions can be managed by gargling after inhalation, which washes away the orally deposited drug [3]. The most difficult local side effect to manage is hoarseness [4], which is caused by drug deposition on the vocal cords.…”
Section: Introductionmentioning
confidence: 98%
“…Hoarseness is a severe subjective symptom and may sometimes cause the self-interruption of inhalation therapy. Previous studies demonstrated that many factors, including age, gender, drug, and the dosage form, caused hoarseness [3,[5][6][7]. Furthermore, a higher risk of dysphonia has been associated with the administration of fluticasone propionate than other corticosteroids [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…In order to decrease local adverse effects (dysphonia, stomatitis, and dry mouth), it is recommended to administer medication with a spacer, gargling, rinsing the mouth, and washing the face after inhalation (if nebulizers are used), as well as washing the spacer [ 25 ]. However, no scientifi c evidence for such procedures is available with the exception of gargling, which was shown to be protective for female patients using DPIs [ 35 ]. In children aged 2-5 years, synchronization of breathing with drug delivery is not suffi cient to allow proper administration.…”
Section: New Generation Of Topical Gcsmentioning
confidence: 99%